Teleconsultation: Rejected and Emerging Uses - Sicotte, C.; Lehoux, P. (Methods of Information in Medicine, 2003)
Objective: The aim of this paper is to analyse telemedicine as a new means to improve health care accessibility.Method: A case study design was used to understand how medical specialists perceived, made sense of, and appropriated a teleconsultation system.Results and Conclusions: The technology was used neither in the manner nor to the extent anticipated by its designers. A fundamental modification to the traditional medical consultation process has emerged. Unable to be used as a substitute to the traditional medical consultation process, the teleconsultation system imposes a greater burden on the shoulders of participating physicians who, after a few trials, returned to their traditional mode of practice.
Keywords: Telemedicine; teleconsultation; users’ mediated use; information and communication technology (ICT)